Capital Market Reaction to the Announcement of the Russian Invasion to Ukraine (Case Study on Energy Industry Companies in ASEAN) - Mely Syafitri Wartindas; Agrianti Komalasari; Fitra Dharma (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and test the reaction of the capital market to geopolitical events. The invasion was carried out by Russia into Ukraine on 24 February 2022. The variables tested were abnormal returns before and after the events in energy industry companies in ASEAN. This study uses a different test (paired sample Wilcoxon signed ranked test) to determine the movement of the average abnormal return 11 days before and after the invasion occurred on 24 February 2022. The results obtained based on the different test say that there is no significant effect of the Russian invasion of Ukraine on stock prices. the energy industry in Indonesia, while there was a significant influence from the Russian invasion of Ukraine on the share price of the energy industry in Malaysia and Singapore.